ETIOLOGIA E PATOGENICIDADE DA SECA DE PONTEIROS EM CLONES DE Tectona grandis L.f. (LAMIACEAE) NO EXTREMO NORTE DO ESTADO DE MATO GROSSO - SILVA, JOCIANE ROSSETO DE OLIVEIRA (2023)
Among the forestry species planted, the planting of Tectona grandis L.f. (Lamiaceae) has been expanding in the Midwest and North regions of Brazil. The increase of planting, however, brings forth the occurrence of diseases. The objective of this thesis was to investigate the etiology and pathogenicity of dieback in clones of Tectona grandis L.f. Therefore, symptomatic material was collected in planted clones of T. grandis located in the far north of the state of Mato Grosso. The materials were isolated and later had their pathogenicity and aggressivity tested in two clones of T. grandis. The work was divided into three chapters. In chapter 1, the approach was the species and methodology of isolation and selection of the isolates for testing of pathogenicity and aggressivity. In the isolation of plant tissue with symptoms of dieback, 22 fungi cultures were collected, which were inoculated in 50 cloned saplings of T. grandis at 120 days of staking. Nine of the isolates were selected for testing of pathogenicity. Chapter 2 had as its objectives the determining of the etiology of dieback and the assessment of pathogenicity and aggressivity of the isolates in two clones of T. grandis by artificial inoculation in nursery. For this, 300 saplings of two clones of T. grandis at 120 days of staking were inoculated, using the technique of mycelium discs with the nine selected isolates, which were characterized on a molecular level. At the 30 and 60-day mark after inoculation, external and internal lesions, slump formation, and internal symptomatic area of the stem shaft were analyzed. The nine isolates were tested and presented different levels of aggressivity, also containing influence from the clone, as well as the variable external or internal lesion and lump formation. The isolates, which were identified as Fusarium proliferatum and Fusarium graminearum, presented different levels of pathogenicity and the Coprinellus radianswere considered non-aggressive. Chapter 3 had as its objective the anatomical analysis of tissue cuts from saplings of two artificially inoculated clones. Anatomical cuts were made at the transversal and tangential longitude in the cloned inoculated saplings. There were no observed alterations or deformation in the axial parenchyma, radial, fiber and vessel tissues of the xylem of inoculated saplings with fungal mycelium. In the anatomical tissues, the occurrence of tylosis with obstruction of lumen of the elements of the xylem vessels was observed.